2021
DOI: 10.1093/qjmed/hcab113.013
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasonography as Tool for Follow Up of Ventilated Neonates for Prediction of Weaning Readiness

Abstract: Background Timing is crucial when deciding if a patient can be successfully extubated. Both premature discontinuation and unnecessary delay of mechanical ventilation weaning have been associated with poor outcome. There are no enough guidelines for the assessment of readiness of newborns for extubation. The degree of lung aeration loss in different clinical conditions can be quantified via lung ultrasound (LUS). Objectives To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Several meta‐analysis have described the varying diagnostic capabilities of LU in conditions such as transient tachypnea of the newborn, 14–16 respiratory distress syndrome (RDS), 17,18 bronchopulmonary dysplasia, 19 and early surfactant replacement prediction 20,21 . Moreover, recent studies have indicated that LU is a promising tool for prediction of extubation outcomes (success or failure) in neonates 22–29 . These recent findings in neonates are consistent with recent systematic review in adults which concluded that LU can assist in determining the ideal time for extubation 30 .…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…Several meta‐analysis have described the varying diagnostic capabilities of LU in conditions such as transient tachypnea of the newborn, 14–16 respiratory distress syndrome (RDS), 17,18 bronchopulmonary dysplasia, 19 and early surfactant replacement prediction 20,21 . Moreover, recent studies have indicated that LU is a promising tool for prediction of extubation outcomes (success or failure) in neonates 22–29 . These recent findings in neonates are consistent with recent systematic review in adults which concluded that LU can assist in determining the ideal time for extubation 30 .…”
Section: Introductionsupporting
confidence: 54%
“…The literature search retrieved 659 potential records. After removing duplicates, screening abstracts, and evaluating subsequent full texts, 8 studies comprising 564 neonates [22][23][24][25][26][27][28][29] were included in the metaanalysis. A detailed flow diagram outlining the study inclusion process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations